(untitled) (Web of Technology: Multidimensional Research Journal, 2026)
The alignment between the Sustainable Development Goals (SDGs) and the professional skills demanded by a sustainable economy constitutes one of the most urgent and undertheorised challenges in contemporary workforce development and higher vocational education. The transition toward net-zero economies, circular production systems, inclusive social services, and digitally mediated value chains all mandated by the 2030 Agenda creates demands for professional competencies that existing vocational training and higher education systems are largely unprepared to supply. This article investigates the intersection of SDG-driven economic transformation and professional skill formation, proposing a comprehensive Sustainable Professional Competency (SPC) framework that identifies the cross-sectoral, sector-specific, and enabling competencies required for SDG-aligned employment.